Survival with low- and high-flux dialysis - Sánchez-Álvarez, Emilio (2021)
FUNDING COSMOS is sponsored by the Bone and Mineral Research Unit (Hospital Universitario Central de Asturias), SAFIM (Sociedad Asturiana Fomento Investigaciones O´ seas), the European Renal Association–European Dialysis and Transplant Association, the National Program of I þ D þ I 2008–2011 and Instituto de Salud Carlos III (ISCIII), the ISCIII Retic REDinREN (RD06/0016/1013, RD12/0021/0023 and RD16/ 0009/0017), the ISCIII (ICI14/00107, PI17/00384 and PI20/ 00633), Fondo Europeo de Desarrollo Regional (FEDER), Plan Estatal de I þ D þ I 2013–2016, Plan de Ciencia, Tecnologia e Innovacion 2013–2017 y 2018–2022 del Principado de Asturias (GRUPIN14-028, IDI-2018-000152), Fundacio´n Renal I ´nigo A ~ ´ lvarez de Toledo (FRIAT) and the Spanish Society of Nephrology (Estudio Estrate´gico de la SEN). Logistics (meetings, secretarial help, printing of materials, development of website for data entry, etc.) have been financially supported by AMGEN Europe and FRIAT. The authors are not aware of any additional relationships, funding or financial holdings that might be perceived as affecting the objectivity of this study. COSMOS participating centres: see Supplementary Appendix.